Educação Ambiental ao redor do mundo: uma análise sobre a temática ambiental a partir de culturas não eurocentradas - Macedo, Felipe Nucci de (Universidade Federal de São Carlos, 2025)
The interactions between human beings and the environment occur in an extremely complex manner and entail a broad and profound interdisciplinary analysis regarding the understanding of the present and the interactions involved. Given that education is a fundamentally social factor and key to understanding the world, Environmental Education has increasingly gained prominence in all societies, encompassing a variety of historical, cultural, social, economic, and religious contexts over time and around the world. In Brazil, three major political-pedagogical macrotrends in Environmental Education are widely referenced, each with its own ideological particularities. Based on this Brazilian context, this work proposes an analytical comparison to understand other perspectives (methodological, practical, and ideological) of Environmental Education around the world—especially in cultures not grounded in Eurocentrism. After a documentary analysis of various environmental practices (located in Asian and African countries, being chosen the following countries for this paper: Kenya, South Africa, Japan, China, and India), it became apparent that many of them tend to adopt a view similar to that seen in Brazil: a predominantly pragmatic view of Environmental Education, flirting with neoliberal ideologies and not framing the discussion in a political manner, always seeking economic viability. Finally, this study enriches the field of Environmental Education by offering a comparative and analytical-reflective analysis of various educational practices in different global contexts, highlighting the importance of an intercultural dialogue that values and respects the multiple ways of understanding and experiencing the relationships with the environment in its all-encompassing conception.
Environmental Education around the world: an analysis of environmental issues from non-Eurocentric cultures
Keywords: Meio ambiente; Decolonialidade; Educação Ambiental; Cultura não Eurocentrada; Environment; Decoloniality; Environmental Education; Non Eurocentric Culture; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO